Pengaruh Pengetahuan Perpajakan Pelayanan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajibb Pajak Orang Pribadi (Studi KPP Pratama Malang Utara) - Indri Hapsari (Universitas Islam Malang, 2017)
ABSTRACTTax is a source of state income used to finance all state activities and statedevelopment. Because it is very important to maintain and improve. In this study will bediscussed several factors affecting the compulsory habit is